Genetic problems at present and their challenges in the future: Thalassemia as a model - I Wahidiyat; P A Wahidiyat (Indonesian Pediatric Society Publishing House, 2016)
Compared to the infectious diseases, genetic disorders are not so frequently encountered in the clinic, so that there has been a trend that they are neglected by people or even by the authorities. Our government is still fighting against infectious diseases and nutritional disorders. The immunization programs of the government have indeed reduced the occurence of many infectious dis- eases. Actually, the government has to begin to think how to handle the emerging genetic disorders, after having eradicating infectious diseases.